Ecologies of creative music practice : mattering music - Lovett, Matthew (New York, NY : Routledge, 2024)
"Ecologies of Creative Music Practice: Mattering Music explores music as a dynamic practice embedded in contemporary ecological contexts, one that both responds to, and creates change within the ecologies in which it is created and consumed. This highly interdisciplinary analysis includes theoretical and practical considerations-from blockchain technology and digital platform commerce to artificial intelligence and the future of work, to sustainability and political ecology-as well as contemporary philosophical paradigms, guiding its investigation through three main lenses: How can music work as a conceptual tool to interrogate and respond to our changing global environment? How have transformations in our digital environment affected how we produce, distribute and consume music? How does music relate to matters of political ecology and environmental change? Within this framework, music is positioned as a starting point from which to examine a range of contexts and environments, offering new perspectives on contemporary technological and ecological discourse. Ecologies of Creative Music Practice: Mattering Music is a valuable text for advanced undergraduates, postgraduates, researchers and practitioners concerned with producing, performing, sharing and listening to music"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Music -- Environmental aspects; Ecomusicology; Ecology -- Philosophy; Soundscapes (Music) -- History and criticism